AssessingtheAcceptanceofaProposedAttendance TrackingAppbytheAdministrationstaff,Teachers, andStudentsattheDepartmentofLettersand EnglishLanguage,UniversityAmarTelidjiLaghouat, Algeria - Behitila,Rania; Nouioua,Amira Hiba (Faculty of Letters and Foreign Languages Department of English, 2025)
The aim of this study is to examine the perspectives of administration staff, teachers, and students at the Department of Letters and English Language, University Amar Telidji Laghouat (Algeria) regarding the use of a proposed application for attendance tracking. This study employs a mixed-methods approach to evaluate the perceptions of its ease of use, usefulness, and potential for improving attendance management processes. Based on the Technology Acceptance Model (TAM) and the Unified TheoryofAcceptanceandUse ofTechnology (UTAUT),this...Resultshowsthatthe application will significantly improve attendance records accuracy, efficiency and accessibility while reducing administrative burden. However, factors including user training, technical infrastructure and privacy concerns were raised as implementation barriers that needed to be overcome. These findings highlight how we can design the app better and how adoption strategies can be practiced, but mainly they prove that each solution should be localized based on the universities interests in Algeria. This study also adds to the wider body of educational technology research by providing an overlooked perspective on technology acceptance in a non-Western context, with implicationsforpracticesaimedatincorporatingdigitaltoolsintoacademicsettings